Bilingualism, monoliteracy, and third language writing: A case from Turkish-Persian context in Iran - Fatemeh Poorebrahim; Mohammad Afsharrad; Behzad Ghonsooly (Indonesian Journal of Applied Linguistics)
Studies on third language (L3) acquisition have shown that biliteracy has a facilitative effect on L3 writing. By comparing performances of bilinguals and monolinguals in subsequent language (English) writing, this study attempts to find whether being bilingual but not biliterate is of help to L3 writing. To this end, 52 Turk-Fars bilingual and 57 Fars monolingual females participated in the study. Data were collected through the participants’ compositions and think-aloud protocols. A series of Mann Whitney U tests were employed to compare the groups’ total writing scores and scores in different components of writing. The results of the study revealed that bilinguals performed better than monolinguals in total writing, organization, and mechanics. However, there was no significant difference between the two groups in content, discourse, syntax, and vocabulary of their compositions. This indicates that being bilingual without necessarily being biliterate is of help to L3 writing. Moreover, it was found that English language was the most frequently used medium of thought while writing in English. The findings of this study indicate the need for developing localized bilingual education systems so that bilinguals can take maximum advantage of their background languages in the process of L3 learning.